Fermentation Technology and Functional Foods - Domenico Giuffrè; Angelo Maria Giuffrè (Frontiers in Bioscience-Elite, 2024)
Food is an integral part of our civilization. It is a cultural phenomenon that, while having evolved, is associated with societal traditions and identity. This work analyzes studies conducted to highlight the health properties of the most common ethnic foods. Although these foods were originally created from the need to preserve perishable produce, presently, we know that the fermentation process makes them nutritionally more complete. The basis of these transformations lies in that vast range of prokaryotic and eukaryotic microorganisms that, similar to small biochemical factories, can transform the initial nutrients into metabolically more active biomolecules through fermentation. Although naturally occurring microbes work together for mutual benefit, environmental conditions enhance or inhibit their development. Starting from a selection of microorganisms naturally present on a substrate, we attempt to select the most suitable species to obtain a fermented food with the best nutritional qualities and the richest in nutraceuticals.